(3GdYRjR GdeMdjs - (3YRjR GdOjf (B((3YdGA GdOjf(B) (3Hf Gdcejdj GdefUhQj Hf GdoeNdWI GdeGdcj, eMeO Hf YHO Gddg Hf MSfs
(3ChdgG (B:s
(3aEfj cfJ bHd Qbe gPg GdChQGb, ehdYkG HYLGFH GdBaGb hZQGFH GdGJaGb ef LgGJ GdCQV hHbGYgG, heOfgG hVjGYgG aLYdJ gPG GdJCdja efGSHkG dhbJ GdePGcQI s
(3BNQgG (B:s
(3hONdhG eUQ hge SHYhf hNQLhG eY bhe ehSi Hf YeQGf, Ydi fHjfG hYdjg GdUdGI hGdSdGe ceG bGd JYGdi dYHGOg, GdBjI hEdjg GdeQLY hGdeBH s
(3aj GdeMGVQGJ (B- (3aj GdSeQ (B- (3Ydi CHhGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B100 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B34 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1140s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs